Konsep Kesantunan Komunikasi Berdasarkan Lafaz Al-Ta’dil Di Sisi Ibn Hajar Al-‘Asqalani - Abu Dzar Ahmad; Mohammad Haafiz Aminuddin Mohd Azmi; Muhamad Razif Ahmad (USIM Press, 2024)
Vol 7. No. 1 (June 2022)